Answer :
Simplifying
4+-7=8t+3
Reorder the Terms
-7+4=8t+3
Reorder The terms again
-7+4t=3+8t
Solving for the variable T
Move all terms containing t to the left, and all other terms to the right
Add -8t to each side of the equation
-7+4t+-8t=3+8t+-8t
Combine like terms
4t+-8t=-4t
7+-4t=3+8t+-8t
Combine like terms
8t+-8t=0
-7+-4t=3+0
-7+-4t=3
Add 7 to each side of the equation
-7+7+-4t=3+7
Combine like terms
0+-4t=3+7
-4t=3+7
Combine like terms 3+7=10
-4t+10
Divide each side by 4
t= -2.5
Simplifying
t= -25
4+-7=8t+3
Reorder the Terms
-7+4=8t+3
Reorder The terms again
-7+4t=3+8t
Solving for the variable T
Move all terms containing t to the left, and all other terms to the right
Add -8t to each side of the equation
-7+4t+-8t=3+8t+-8t
Combine like terms
4t+-8t=-4t
7+-4t=3+8t+-8t
Combine like terms
8t+-8t=0
-7+-4t=3+0
-7+-4t=3
Add 7 to each side of the equation
-7+7+-4t=3+7
Combine like terms
0+-4t=3+7
-4t=3+7
Combine like terms 3+7=10
-4t+10
Divide each side by 4
t= -2.5
Simplifying
t= -25
Okay, so we have
4t - 7 = 8t + 3
We Need to Simplify.
Add 7 to both sides to begin.
4t = 8t + 3 + 7
Now, Combine 7 + 3
4t = 8t + 10
Combine the ts
-4t = 10
Divide.
-4t/-4 = 1t = t
t = 10/-4
10/-4 = -2 and 2/4
-2 and 2/4 = -2.5
t = -2.5
4t - 7 = 8t + 3
We Need to Simplify.
Add 7 to both sides to begin.
4t = 8t + 3 + 7
Now, Combine 7 + 3
4t = 8t + 10
Combine the ts
-4t = 10
Divide.
-4t/-4 = 1t = t
t = 10/-4
10/-4 = -2 and 2/4
-2 and 2/4 = -2.5
t = -2.5